The Problem of Intertextuality in Modern Literature - Sharipov Mamur Mansurovich (Universitas Muhammadiyah Sidoarjo, 2022)
The article provides a brief overview of English and Uzbek literature, as well as comments on the problem of intertextuality in English and Uzbek literature. In addition, examples are given and analyzed based on a comparative analysis of the modern literature.